Color‐Coded Fluorescence Imaging of Lymph‐Node Metastasis, Angiogenesis, and Its Drug‐Induced Inhibition. Issue 3 (March 2014) - Aki, Ryoichi; Amoh, Yasuyuki; Bouvet, Michael; Katsuoka, Kensei; Hoffman, Robert M.
ABSTRACT Lymph nodes are often the first target of metastatic cancer which can then remetastasize to distant organs. The progression of lymph node metastasis is dependent on sufficient blood supply provided by angiogenesis. In the present study, we have developed a color‐coded imaging model to visualize angiogenesis of lymph nodes metastasis using green fluorescent protein (GFP) and red fluorescent protein (RFP). Transgenic mice carrying GFP under the control of the nestin promoter (ND‐GFP mice) were used as hosts. Nascent blood vessels express GFP in these mice. B16F10‐RFP melanoma cells were injected into the efferent lymph vessel of the inguinal lymph node of the ND‐GFP nude mice, whereby the melanoma cells trafficked to the axillary lymph node. Three days after melanoma implantation, ND‐GFP‐expressing nascent blood vessels were imaged in the axillary lymph nodes. Seven days after implantation, ND‐GFP‐expressing nascent blood vessels formed a network in the lymph nodes. ND‐GFP‐positive blood vessels surrounded the tumor mass by 14 days after implantation. However, by 28 days after implantation, ND‐GFP expression was diminished as the blood vessels matured. Treatment with doxorubicin significantly decreased the mean nascent blood vessel length per tumor volume. These results show that the dual‐color ND‐GFP blood vessels/RFP‐tumor model is a powerful tool to visualize and quantitate angiogenesis of metastatic lymph nodes as well as for evaluation of its inhibition. J. Cell. Biochem. 115: 457–463, 2014. © 2013 Wiley Periodicals, Inc.